The new frontier of platform policy - Matthew Marinett (Internet Policy Review, 2021)
Platform policies aimed at the misbehaviour of users that occurs off of the platform, especially offline abuse, are a relatively new and understudied phenomenon that may represent a new frontier of platform policy. However, policies of this nature raise unique problems in comparison to on-platform content moderation that exacerbate existing concerns about the accountability of platforms by demanding both heightened due process for the accused and strong privacy and safety protections for complainants. This article discusses these challenges through the case study of Twitch.tv, and argues that further steps must be taken to ensure accountability to users and the public when such policies are implemented.
Keywords: 300; Platform policies; Social media; Twitch; Platform governance; Off-platform behaviour